Three New Species of Tursiocola (Bacillariophyta) from the Skin of the West Indian Manatee (Trichechus manatus) - Frankovich, Thomas Anthony; Sullivan, Michael J.; Stacy, Nicole (Phytotaxa, 2015)
Three new species of Tursiocola are described from the skin of the West Indian manatee bringing the total number of known species in the genus to seven. The range of morphological diversity within the genus is greatly expanded. The number of poroid rows on the copulae is no longer a valid characteristic for the separation of Tursiocola from the ceticolous genus Epiphalaina. The presence of a butterfly-like structure in the central area of the former is at present the best criterion for separating the 2 genera. The 3 new Tursiocola species accounted for nearly 90% of all diatom valves on the manatee skin. No other diatom taxa previously described as new from the skin of cetaceans were present on the manatee.